2022
DOI: 10.1002/jwmg.22222
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale resource selection and behavioral tradeoffs of eastern wild turkey broods

Abstract: Resource heterogeneity across the landscape prompts animals to make behavioral tradeoffs to survive and reproduce. Behavioral thermoregulation can buffer organisms from thermal extremes but may conflict with other essential activities such as predator avoidance or foraging, and necessitate tradeoffs among resource requirements. We evaluated patterns of habitat selection relative to thermal conditions, forage availability, and concealment cover for female eastern wild turkeys (Meleagris gallopavo silvestris) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…Sites with higher NDVI values were initially selected by brooding females, but selection of these sites decreased markedly as broods aged. Higher NDVI values represent denser vegetation that brooding females likely prioritize as both foraging and concealment cover (Nelson et al 2022). Decreasing selection for higher NDVI values as broods age could represent broods shifting predator avoidance strategies as they develop and body size increases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sites with higher NDVI values were initially selected by brooding females, but selection of these sites decreased markedly as broods aged. Higher NDVI values represent denser vegetation that brooding females likely prioritize as both foraging and concealment cover (Nelson et al 2022). Decreasing selection for higher NDVI values as broods age could represent broods shifting predator avoidance strategies as they develop and body size increases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hardwoods on our study area had the lowest maximum visual obstruction (Table A1) and thus likely provided easier visual detection of predators by brooding females than in other vegetation communities. Additionally, Nelson et al (2022) reported that brooding females selected areas with higher grass and lower woody understory groundcover composition. Therefore, brooding females may have consistently selected for hardwoods because they provided the most favorable thermoregulatory and foraging conditions for poults given the limited presence of pasture and early successional sites on our study area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations